Boron complexes of aromatic 5-substituted iminopyrrolyl ligands: synthesis, structure, and luminescence properties. Issue 35 (20th August 2019) - Rodrigues, Ana I.; Figueira, Cláudia A.; Gomes, Clara S. B.; Suresh, D.; Ferreira, Bruno; Di Paolo, Roberto E.; Pereira, Daniel de Sa; Dias, Fernando B.; Calhorda, Maria José; Morgado, Jorge; Maçanita, António L.; Gomes, Pedro T.
Abstract : Highly fluorescent new 5-substituted 2-iminopyrrolyl boron complexes were tested in OLEDs exhibiting luminances up to 23 530 cd m −2 and an EQEmax of 2.75%. Abstract : A group of new mononuclear boron chelate compounds [BPh2 κ 2 N, N ′-5-R-NC4 H2 -2-C(H){N–Ar] (R = Ar = C6 H5 7 ; R = C6 H5, Ar = 2, 6-iPr2 C6 H3 8 ; R = Anthracen-9-yl (Anthr), Ar = C6 H5 9 ; R = Anthr, Ar = 2, 6-iPr2 C6 H3 10 ) were synthesized via the reaction of B(C6 H5 )3 with the corresponding 5-substituted 2-( N -arylformimino)pyrrole ligand precursors3–6 . These complexes were prepared in order to evaluate the luminescence potential derived from the substitution of the position 5 of the pyrrolyl ring with an aromatic group. Compounds7–10 were photophysically characterized in solution and in the solid state. The 5-phenyl-2-iminopyrrolyl-BPh2 complexes7 and8 are blue emitters and have enhanced photoluminescence quantum yields in the solid state ( Φ PL ) up to 0.95, whereas the 5-anthracenyl derivatives9 and10 have green-bluish fluorescence and a Φ PL of 0.49 and 0.24, respectively. DFT and TDDFT studies were performed, considering the effect of solvent and dispersion, in order to show how the geometries of compounds7–10 changed from the ground to the excited state, to assign electronic transitions, and to rationalize the observed luminescence. These materials were applied in organic light-emitting diodes (OLEDs), with various device structures, the best showing an external quantum efficiency of 2.75% together with a high luminance of 23 530 cd m −2 .